Fatigue dan Aktivitas Fisik pada Pasien Pasca Infark Miokard - Dian Novita Putri; Emil Huriani; Esi Afriyanti (Fakultas Keperawatan Universitas Andalas, 2018)
Post myocardial infarction patient commonly performs mild physical activity. Physical activity is known to reduce the risk of acute myocardial infarction. More than half of post myocardial infarction patient experienced fatigue, thus becoming a barrier to physical activity. The purpose of this study was to determine the relationship of fatigue with physical activity in patients after myocardial infarction. Study design was quantitative with correlation method and cross-sectional approach. Sample was of 97 patients who experienced previous myocardial infarction. The data were collected using the Multidimensional Fatigue Inventory-20 questionnaire and the International Physical Activity Questionnaire (IPAQ) questionnaire. The univariate analysis was presented with frequency distribution and bivariat tables using the Spearman test. The results showed that there was a significant relationship between fatigue and physical activity (p = 0,000). This means that patients with high fatigue are at risk of having decreased physical activity. Therefore, it is expected that there will be intervention and information provided by health workers to the family to motivate patients to be able to move without difficulties.